Imidazole/benzimidazole-modified cyclotriphosphazenes as highly selective fluorescent probes for Cu2+: synthesis, configurational isomers, and crystal structures. Issue 28 (3rd July 2017) - Uslu, Aylin; Tümay, Süreyya Oğuz; Şenocak, Ahmet; Yuksel, Fatma; Özcan, Elif; Yeşilot, Serkan
Abstract : We present a comprehensive work and discuss the fluoroprobe properties of synthesized compounds for copper ion detection with a stereochemical approach using X-ray crystallographic analysis results. Abstract : Configurational isomers ( cis and trans ) of imidazole- or benzimidazole-modified cyclotriphosphazenes (3a, 4a or3b, 4b ) were designed, synthesized and investigated as fluorescent probes for metal ions. The newly synthesized compounds were characterized by 1 H and 31 P NMR, and MALDI MS spectrometry. The configurations of geometric isomers were analyzed by X-ray crystallography and 31 P NMR spectroscopy on addition of CSA. The photophysical behaviour and metal ion selectivity of the compounds were investigated by UV/vis and fluorescence spectroscopy. Among the examined 20 metal ions, the fluorescence emissions of the isomer mixtures were quenched by Cu 2+ together with Fe 2+, Fe 3+, Zn 2+ and Ni 2+ ions, but each individual isomer (3a, b and4a, b ) exhibited an on–off-type fluorescence response with high selectivity towards only Cu 2+ with a low limit of detection ranging from 1.27 μM to 2.04 μM. The complex stoichiometries of3a, b and4a, b with Cu 2+ were determined as 1 : 1 (L/M) using the method of continuous variation (Job's plot) and density functional theory (DFT) calculations; moreover the complex formation of4a with Cu 2+ was unambiguously determined by X-ray crystallographic analysis that is consistent with the results obtained by the Job's plots as well as DFT.